Sequential psychological and pharmacological therapies for comorbid and primary insomnia: study protocol for a randomized controlled trial. Issue 1 (December 2016) - Morin, Charles; Edinger, Jack; Krystal, Andrew; Buysse, Daniel; Beaulieu-Bonneau, Simon; Ivers, Hans
Abstract Background Chronic insomnia is a prevalent disorder associated with significant psychosocial, health, and economic impacts. Cognitive behavioral therapies (CBTs) and benzodiazepine receptor agonist (BzRA) medications are the most widely supported therapeutic approaches for insomnia management. However, few investigations have directly compared their relative and combined benefits, and even fewer have tested the benefits of sequential treatment for those who do not respond to initial insomnia therapy. Moreover, insomnia treatment studies have been limited by small, highly screened study samples, fixed-dose, and fixed-agent pharmacotherapy strategies that do not represent usual clinical practices. This study will address these limitations. Methods/design This is a two-site randomized controlled trial, which will enroll 224 adults who meet the criteria for a chronic insomnia disorder with or without comorbid psychiatric disorders. Prospective participants will complete clinical assessments and polysomnography and then will be randomly assigned to first-stage therapy involving either behavioral therapy (BT) or zolpidem. Treatment outcomes will be assessed after 6 weeks, and treatment remitters will be followed for the next 12 months on maintenance therapy. Those not achieving remission will be offered randomization to a second, 6-week treatment, again involving either pharmacotherapy (zolpidem or trazodone) or psychological therapy (BT or cognitive therapy (CT)). All participants will be re-evaluated 12 weeks after the protocol initiation and at 3-, 6-, 9-, and 12-month follow-ups. Insomnia remission, defined categorically as a score < 8 on the Insomnia Severity Index, a patient-reported outcome, will serve as the primary endpoint for treatment comparisons. Secondary outcomes will include sleep parameters derived from daily sleep diaries and from polysomnography, subjective measures of fatigue, mood, quality of life, and functional impairments; and measures of adverse events; dropout rates; and treatment acceptability. Centrally trained therapists will administer therapies according to manualized, albeit flexible, treatment algorithms. Discussion This clinical trial will provide new information about optimal treatment sequencing and will have direct implication for the development of clinical guidelines for managing chronic insomnia with and without comorbid psychiatric conditions. Trial Registration ClinicalTrials.gov Identifier:NCT01651442, Protocol version 4, 20 April 2011, registered 26 June 2012